Monitoring of the State of the Left-Bank Confluents of the Upper Yenisei Basin in the Zone Of Impact of the Coal Industry Enterprise - O. Ondar, Sergey; O. Khovalyg, Aldynay; V. Ondar, Urana; I. Sodnam, Natalya (International Journal of Engineering and Technology, 2018)
Mining leads to technogenic transformation of ecosystems and causes environmentally dangerous situations. A separate task in the field operation is the monitoring of aquatic ecosystems as reservoirs of phytoplankton and hydrobionts as well as a link between surface and ground water. Therefore, monitoring of ecosystems which are subject to technogenic factors is an urgent task for further forecasting of their transformation and will also allow selecting and adapting optimal technologies for their reclamation. The article presents the results of hydro-chemical indicators of the left-bank confluents of the Upper Yenisei basin for 2015-2017 in the conditions of influence of coal-mining enterprise "Mezhegeyugol". It has been revealed that the quality of surface waters (color, turbidity) deteriorates, the ionic composition and the pH level of the water are subject to seasonal fluctuations, exceeding MPC (maximum permissible concentration) of ammonium and total iron ions in the investigated waters is identified as well as contamination with coal dust while the content of chemical elements does not exceed MPC.Â Â